(In)Equality at the intersection of race and space in Johannesburg. Issue 3 (2nd September 2017) - Madlalate, Ralph
Abstract: This article explores the role of law in producing post-apartheid Johannesburg, a social space marked by South Africa's history of racial injustice. It recasts Johannesburg as a living social product which reveals patterns of power and disadvantage in an inegalitarian society. It traces the production of Johannesburg over decades of social activity, arguing that this process of production has been shaped by race. This article then reflects on the transformative potential of law and its promise of equality in the constitutional era which is plagued by racial inequality. It adopts a theory of law as a normative discourse, in order to analyse the law's subtle mapping of the boundaries of privilege and disadvantage. It concludes by suggesting that the law is not an inherently beneficial force but represents a site of contest which may reproduce spatial inequality rather than address it.